Distinctively Political Normativity in Political Realism: Unattractive or Redundant. - Erman, Eva; Möller, Niklas (Ethical Theory & Moral Practice, 2022)
Political realists' rejection of the so-called 'ethics first' approach of political moralists (mainstream liberals), has raised concerns about their own source of normativity. Some realists have responded to such concerns by theorizing a distinctively political normativity. According to this view, politics is seen as an autonomous, independent domain with its own evaluative standards. Therefore, it is in this source, rather than in some moral values 'outside' of this domain, that normative justification should be sought when theorizing justice, democracy, political legitimacy, and the like. For realists the question about a distinctively political normativity is important, because they take the fact that politics is a distinct affair to have severe consequences for both how to approach the subject matter as such and for which principles and values can be justified. Still, realists have had a hard time clarifying what this distinctively political normativity consists of and why, more precisely, it matters. The aim of this paper is to take some further steps in answering these questions. We argue that realists have the choice of committing themselves to one of two coherent notions of distinctively political normativity: one that is independent of moral values, where political normativity is taken to be a kind of instrumental normativity; another where the distinctness still retains a justificatory dependence on moral values. We argue that the former notion is unattractive since the costs of commitment will be too high (first claim), and that the latter notion is sound but redundant since no moralist would ever reject it (second claim). Furthermore, we end the paper by discussing what we see as the most fruitful way of approaching political and moral normativity in political theory.